Pericardial effusion in a patient of celiac disease and hypothyroidism: A case report (Indian Journal of Case Reports, 2024)
Celiac disease (CD) can be defined as an autoimmune chronic disorder in gluten-intolerant individuals producing malabsorption of nutrients and vitamins. The presence of CD in individuals causes an alteration in the absorption and pharmacokinetics of certain drugs. This poses a great challenge in maintaining serum thyrotropin levels in hypothyroidism patients on replacement therapy with levothyroxine (LT4). In this report, we present the case of a 39-year-old woman with hypothyroidism, pericardial effusion, and (previously unrecognized) CD. Our patient was a known case of hypothyroidism with a history of previous hospitalization for an episode of acute gastroenteritis. In our clinic, after an initial workup, the patient was continued on LT4 supplement, oral iron, and multivitamins. During her follow-up visit, when an anti-tissue transglutaminase IgA-positive report was available, a gluten-free diet was advised. Following this, the clinical condition of the patient improved drastically, accompanied by a fall in elevated thyroid-stimulating hormone (TSH) levels. This case highlights the necessity of understanding the etiology of rising serum TSH levels, hence ruling out malabsorption. Pericardial effusion, being a rare complication of hypothyroidism and CD, may lead to adverse cardiac events, hence resulting in hospitalization and patient disability.